FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN PERAWAT RAWAT INAP RS MARINIR CILANDAK PADA MASA PANDEMI COVID-19 TAHUN 2021 - Flavia Stefanie Ananda Utami (2022)
The purpose of this study was to analyse the assocciation between individual factors and work factors on fatigue in inpatient nurses at the Cilandak Marine Hospital. This study used a cross sectional study design. The data analysis used in this research is the chi-square and the Fisher Probability Exact Test. The sampling technique used is purposive sampling. The number of samples in this study were 80 inpatient nurses. The results of univariate analysis showed that inpatient nurses experienced more light fatigue 58.8%, female sex as much as 91,2%, age 35 years as many as 51,2%, abnormal nutritional status as much as 52,5%, working period <13 years as much as 51,2%, and heavy mental workload as much as 53,8%. The results of the bivariate analysis showed that there was a assocciation between age (p=0.003), nutritional status (p=0.019), and mental workload (p=0.03). Sex (p=0.439) and working period (p=1) had no assocciation with work fatigue. Nurses are advised to use rest time as well as possible, consume balanced nutrition, and utilize sleep time efficiently to minimize the risk of work fatigue for nurses.